2011
DOI: 10.1308/003588411x565969
|View full text |Cite
|
Sign up to set email alerts
|

Parotid cancer treatment with surgery followed by radiotherapy in Oxford over 15 years

Abstract: INTRODUCTION Primary parotid malignancies represent a rare diagnosis, making high-quality comparative research unfeasible. There is little UK-based evidence to guide practice. A review was therefore undertaken of a large series of patients treated by a multidisciplinary team in a National Health Service tertiary referral centre. PATIENTS AND METHODS Retrospective patient record review at the John Radcliffe Hospital in Oxford identified 401 patients who had undergone parotidectomy between 1995 and 2010, of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The role of postoperative radiotherapy as an independent factor in locoregional control of tumors of the salivary glands and, especially, of the parotid glands, is based on retrospective studies [3][4][5][6][7][8][9][10][11]. The low incidence of these tumors makes it difficult to conduct prospective randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…The role of postoperative radiotherapy as an independent factor in locoregional control of tumors of the salivary glands and, especially, of the parotid glands, is based on retrospective studies [3][4][5][6][7][8][9][10][11]. The low incidence of these tumors makes it difficult to conduct prospective randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy significantly improved regional control in the clinically positive (N+) neck (86 vs. 62% for surgery alone). A more recent study of 50 patients with parotid gland cancer treated in the United Kingdom demonstrated excellent local control (96%) with surgery and postoperative radiotherapy [12] .…”
Section: The Clinically Positive Neckmentioning
confidence: 97%
“…In many of these cases, the first echelon is represented by the intraparotid lymph nodes. The mean numbers of intraparotid lymph nodes that have been reported are 7 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in the superficial lobe and 2 (range, 0-9) in the deep lobe [38] . Furthermore, a statistically significant correlation (p = 0.005) has been observed between the presence of intraparotid metastatic nodes and neck node metastases [39] .…”
Section: Sentinel Node Biopsy In Primary Parotid Cancermentioning
confidence: 99%
“…Though complete surgical excision of the tumor along with an adequate margin of histologically normal tissue remains the main aim of surgical treatment, much of the surgical literature details management plans tailored to specific histologic diagnoses although this diagnosis is usually not available definitively until the surgical excision has occurred [34]. Although the aim of surgical removal with clear margins would be agreed, the extent to which this may be achieved is complicated by the relationship between the tumor and the facial nerve.…”
Section: Parotidmentioning
confidence: 99%